Autoclave-chemical hydrolysis of chicken feather for protein hydrolysate production - Cheong, Chooi Wei (2018)
Millions tonnes of feather waste are generated every year. Various treatments on feather waste have been developed in order to add value to them. However, these methods have their pros and cons. Autoclave-chemical treatment could hydrolyse feather within a short period but harsh conditions could lead to excessive destruction on protein and amino acids. Biological treatment is an eco-friendly treatment which could hydrolyse feather with minimum protein and amino acid destruction but it required a long reaction time. Therefore, treatment modification is necessary in order to enhance the feather hydrolysis and produce feather hydrolysate consists high amount of protein and amino acids. The objectives of this study were to investigate the effect of autoclave-chemical treatment on chicken feather hydrolysis and to examine the effect of autoclave-alkaline as pretreatment on enzymatic hydrolysis of chicken feather. Sodium hydroxide (NaOH) was selected based on the screening result and the temperature was fixed at 105°C. The NaOH concentration and autoclave holding time ranged from 0.01 M to 0.10 M and 1 min to 10 min, respectively were used in the subsequent experiments. The effect of autoclave-alkaline treatment (AAT) on feather was investigated using response surface methodology (RSM). NaOH concentration and holding time were the significant parameters in AAT that affect the feather hydrolysis and protein production (p <0.05). The ideal conditions for AAT were 0.08 M of NaOH, 7 min holding time at 105°C in which 85.59% of feather were solubilized and 0.75 g/g of soluble protein with 633.50 mg/g of free amino acid could be recovered from chicken feather. Autoclave-alkaline method was also proposed to be used as pretreatment in this study in order to enhance the performance of the subsequent biological treatment. The effect of autoclave-alkaline as pretreatment on the enzymatic hydrolysis of chicken feather with Savinase® Ultra 16L by RSM was investigated. NaOH concentration was significant parameter that affected the subsequent enzymatic reaction on feather hydrolysis and protein production (p <0.05). The pretreated chicken feather with optimized autoclave-alkaline (0.07 M of NaOH, 2 min holding time at 105°C) could improve Savinase hydrolysis up to 14 times with 80.81% of feather hydrolysis and recovered 0.69 g/g of soluble protein as well as 673.80 mg/g of free amino acid. Therefore, AAT is a potential method for feathers solubilization, as well as, recovery of soluble protein and free amino acid from chicken feather waste. Autoclave-alkaline pretreatment also could enhance enzyme reaction to degrade chicken feather to a great extent and generate feather hydrolysates rich in amino acids.